Method for improving mechanical property of GH4169 nickel-based alloy and product obtained through method

By adding rare earth metal powder to GH4169 nickel-based alloy and using laser melting technology for 3D printing and heat treatment, the problem of insufficient mechanical properties of the existing GH4169 alloy is solved, and the mechanical properties and friction and wear properties of the alloy are significantly improved.

CN119553119APending Publication Date: 2025-03-04SHANXI JIANGHUAI HEAVY IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411589853.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing GH4169 nickel-based alloy cannot meet the high mechanical performance requirements of aerospace products in service in extreme weather.

Method used

By mixing rare earth metal powder with GH4169 nickel-based alloy powder at a mass ratio of 1:20 to 25, 3D printing and rapid molding was performed using selective laser melting technology, and solid solution strengthening and dual aging treatment were performed to prepare GH4169 rare earth strengthening nickel-based alloy.

Benefits of technology

It significantly improves the tensile strength, elongation, hardness and friction wear performance of the alloy, and meets the high mechanical performance requirements of aerospace products in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553119A_ABST
    Figure CN119553119A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the mechanical property of a GH4169 nickel-based alloy and a product obtained through the method, and belongs to the technical field of alloy preparation. The method comprises the following steps that (1) rare earth metal powder and GH4169 nickel-based alloy powder are mixed according to the mass ratio of 1: (20-25), and a mixed material is obtained; 2) taking the mixed material as a raw material, and preparing a GH4169 rare earth reinforced nickel-based alloy sample by adopting laser melting; and (3) the obtained GH4169 rare earth reinforced nickel-based alloy sample is subjected to solution strengthening and double-aging treatment. The GH4169 nickel-based alloy prepared by the method provided by the invention has the mechanical properties of high tensile strength, high hardness, good ductility and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy preparation, and in particular relates to a method for improving the mechanical properties of GH4169 nickel-based alloy and a product obtained therefrom. Background Art

[0002] Selective laser melting technology is an important branch of metal 3D printing. Metal 3D printing is the most promising and cutting-edge technology in additive manufacturing (AM). It is a rapid prototyping technology that uses the concept of layered manufacturing and layer-by-layer stacking. It is developed on the basis of traditional rapid prototyping. It first uses computer drawing software (such as CAD, etc.) to draw the three-dimensional model of the required parts, and then uses special software to slice and discretize the three-dimensional model of the parts in the Z direction and plan its scanning path to obtain data for each section. The obtained data is then imported into the corresponding forming equipment. The equipment will selectively melt each layer of metal powder according to the given data by controlling the laser beam, so that the metal powders are bonded to each other to achieve metallurgical bonding, and then the required metal parts are finally obtained by stacking layers.

[0003] GH4169 alloy is a nickel-based high-temperature alloy. After precipitation strengthening, the metal has good mechanical properties in the temperature range of 253-650℃, and its comprehensive performance is also relatively stable. The yield strength below 650℃ ranks first among deformed high-temperature alloys, and has good fatigue resistance, radiation resistance, oxidation resistance, corrosion resistance, as well as good processing performance and welding performance. Aerospace products need to serve in extreme weather for a long time and withstand complex stress changes, which makes the parts extremely vulnerable to damage. Therefore, the parts need to have extremely high surface stability. Due to the limitations of the use environment, the mechanical properties of GH4169 are required to be high, but ordinary GH4169 alloys cannot meet these requirements. Summary of the invention

[0004] The present invention provides a method for improving the mechanical properties of a GH4169 nickel-based alloy and a product obtained therefrom. The GH4169 nickel-based alloy prepared by the method provided by the present invention has mechanical properties such as high tensile strength, high hardness, and good elongation.

[0005] In order to achieve the above object, the present invention provides a method for improving the mechanical properties of GH4169 nickel-based alloy, comprising the following steps:

[0006] 1) mixing rare earth metal powder and GH4169 nickel-based alloy powder in a mass ratio of 1:20 to 25 to obtain a mixed material;

[0007] 2) Using the mixed material as raw material, laser melting was used to prepare GH4169 rare earth reinforced nickel-based alloy samples;

[0008] 3) The obtained GH4169 rare earth strengthened nickel-based alloy sample was subjected to solid solution strengthening and double aging treatment.

[0009] Preferably, the particle size of the rare earth metal powder in step 1) is 250-300 mesh; the particle size of the GH4169 nickel-based alloy powder is 15-55 μm.

[0010] Preferably, the rare earth metal powder in step 1) is prepared by the following steps:

[0011] a. Place the rare earth metal in hydrogen at 445-455°C to hydrogenate and obtain hydrogenated rare earth;

[0012] b. The hydrogenated rare earth and the olefin dehydrogenating agent are mixed and placed in a vacuum environment of 445 to 455 ° C for dehydrogenation to obtain a dehydrogenated rare earth;

[0013] c. ball milling the dehydrogenated rare earth to obtain rare earth metal powder.

[0014] Preferably, when hydrogenation is performed in step a, the hydrogenation insulation time is 1.5 to 2 hours, the hydrogen flow rate is controlled at 1.0 to 1.5 L / min, and stirring is performed every 0.5 to 1 hour during the hydrogenation process.

[0015] Preferably, the dehydrogenation time in step b is 2 to 4 hours.

[0016] Preferably, in step c, ball milling is performed using nitrogen-filled dry milling.

[0017] Preferably, when laser melting is used to prepare the GH4169 rare earth reinforced nickel-based alloy sample in step 2), the laser power is 1400-1800w, the scanning speed is 8-14mm / s, the powder feeding rate is 1.3-1.8r / min, and the spot diameter is 1.5-2mm.

[0018] Preferably, the temperature during the solid solution strengthening treatment in step 3) is 1080-1150° C. and the time is 0.8-1.4 h.

[0019] Preferably, in the double aging treatment in step 3), the temperature of the first aging treatment is 700-740° C., kept warm for 7-9 hours, and furnace cooled for 1.5-3 hours; the temperature of the second aging treatment is 600-650° C., kept warm for 6-10 hours.

[0020] The present invention also provides a GH4169 nickel-based alloy prepared by any of the methods described above, characterized in that the tensile strength of the GH4169 nickel-based alloy is ≥1980 MPa and the elongation is ≥17%.

[0021] Compared with the prior art, the advantages and positive effects of the present invention are:

[0022] The present invention adds rare earth element powder, mixes it evenly with GH4169 powder by ball milling, adopts selective laser melting technology, and performs 3D printing rapid prototyping on it to prepare a metal sample of GH4169 rare earth strengthened nickel-based alloy. At this time, the main phase organization of the printed metal sample is: matrix phase γ, strengthening phase γ′, γ and γ′ eutectic phase, γ″, δ phase and carbide phase. The prepared metal sample is heat treated (solid solution treatment + aging) to form a new rare earth strengthening phase. At this time, a small amount of residues of strengthening phases such as carbides appear in the organization to form a dislocation line cutting second phase, which significantly improves the friction and wear properties of the alloy. A large amount of γ′ phase and γ″ phase and δ phase will precipitate in the crystal, wherein the γ″ phase is the main strengthening phase, and the γ′ phase and δ phase are secondary strengthening phases. At this time, the metal sample produces fine grain strengthening, solid solution strengthening, precipitation strengthening and second phase strengthening, which further improves the tensile strength, microhardness, friction and wear properties of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The metallographic structure of GH4169 rare earth strengthened nickel-based alloy at different heat treatment and solution treatment temperatures;

[0024] Figure 2 The SEM microstructure of GH4169 rare earth strengthened nickel-based alloy at different heat treatment and solution treatment temperatures;

[0025] Figure 3 is the friction and wear coefficient of GH4169 rare earth reinforced nickel-based alloy at different heat treatment and solution treatment temperatures. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a method for improving the mechanical properties of GH4169 nickel-based alloy, comprising the following steps:

[0028] 1) mixing rare earth metal powder and GH4169 nickel-based alloy powder in a mass ratio of 1:20 to 25 to obtain a mixed material;

[0029] 2) Using the mixed material as raw material, laser melting was used to prepare GH4169 rare earth reinforced nickel-based alloy samples;

[0030] 3) The obtained GH4169 rare earth strengthened nickel-based alloy sample was subjected to solid solution strengthening and double aging treatment.

[0031] The present invention mixes rare earth metal powder and GH4169 nickel-based alloy powder in a mass ratio of 1:20 to 25 to obtain a mixed material. In the present invention, the particle size of the rare earth metal powder is preferably 250 to 300 meshes. In the present invention, the rare earth metal is preferably yttrium, gadolinium, and neodymium. The particle size of the GH4169 nickel-based alloy powder is preferably 15 to 55 μm. In the present invention; the rare earth metal powder is preferably prepared by the following steps:

[0032] a. Place the rare earth metal in hydrogen at 445-455°C to hydrogenate and obtain hydrogenated rare earth;

[0033] b. The hydrogenated rare earth and the olefin dehydrogenating agent are mixed and placed in a vacuum environment of 445 to 455 ° C for dehydrogenation to obtain a dehydrogenated rare earth;

[0034] c. ball milling the dehydrogenated rare earth to obtain rare earth metal powder.

[0035] The quality of rare earth metal powder mainly depends on the powder making method, and the powder making method determines the size, shape, loose density, chemical composition, pressing performance, etc. of the powder particles. Since rare earth metals are more active, their powders are more active, and it is difficult to obtain metal powders of good quality using general mechanical powder making methods. In the present invention, rare earth metal powders are prepared by hydrogen absorption-dehydrogenation, and fragile rare earth hydrides are obtained by hydrogenation. After dehydrogenation, ball milling is performed to obtain rare earth metal powders with a particle size of 250 to 300 meshes. The present invention adopts a mechanochemical method to prepare rare earth metals, which not only saves energy and reduces consumption, but also can prepare high-purity rare earth metal powders of 250 to 300 meshes.

[0036] In the present invention, when hydrogenation is carried out, the hydrogenation insulation time is preferably 1.5 to 2 hours, the hydrogen flow rate is preferably controlled at 1.0 to 1.5 L / min, and stirring is preferably performed every 0.5 to 1 hour during the hydrogenation process. In the present invention, the hydrogenation insulation time is controlled at 1.5 to 2 hours, and the hydrogenation temperature is controlled at 445 to 455°C, so that the rare earth metal hydrogenation effect can be optimized, which is conducive to ensuring the purity of the rare earth metal powder obtained by subsequent dehydrogenation. In the present invention, the dehydrogenation time is preferably 2 to 4 hours. In the present invention, it is preferred to use nitrogen-filled dry milling for ball milling. In the present invention, the mass ratio of the hydrogenated rare earth and the alkene-dehydrogenating agent is preferably 5 to 4: 4 to 3. In the present invention, the alkene-dehydrogenating agent is preferably modified with rare earth metals. The alkene-hydroxy dehydrogenating agent used in the embodiment of the present invention was purchased from the DH334 dehydrogenating agent of Kunshan Sheng'an Biotechnology Co., Ltd.

[0037] In the present invention, adding trace rare earth elements to the nickel-based alloy can reduce the pore defects of the material, improve the density of the alloy and refine the structure, which is helpful to improve its strength. Since the atomic radius of rare earth elements is large, with the addition of trace rare earth elements, the lattice will be distorted, the grain boundary plasticity will increase, the rare earth elements and sulfur elements attract each other, so that some impurities are fixed, and the high-temperature mechanical properties of the alloy are improved.

[0038] After obtaining the mixed material, the present invention uses the mixed material as a raw material and adopts laser melting to prepare a GH4169 rare earth reinforced nickel-based alloy sample. In the present invention, when laser melting is used to prepare the GH4169 rare earth reinforced nickel-based alloy sample, the laser power is preferably 1400-1800w, the scanning speed is preferably 8-14mm / s, the powder feeding amount is preferably 1.3-1.8r / min, and the spot diameter is preferably 1.5-2.1mm; more preferably, the laser power is 1600w, the scanning speed is 10mm / s, the powder feeding amount is 1.5r / min, and the spot diameter is 2mm. The laser melting parameters used in the present invention are conducive to the full melting of the rare earth alloy powder, the formation of a stable structure and lattice structure, and the avoidance of shrinkage, shrinkage holes and faults. If the power is too high, the temperature will rise too quickly during the printing process, causing the melting point of the rare earth alloy material to drop, thus affecting the printing accuracy and surface quality. At the same time, too high power will also cause metal splashing, and the molten metal will fly out of the molten pool into the surrounding area. If the power is too low, the metal material powder may not be completely melted, resulting in a rough surface and internal defects of the product, affecting the material performance.

[0039] After obtaining the GH4169 rare earth strengthened nickel-based alloy sample, the present invention performs solid solution strengthening and double aging treatment on the obtained GH4169 rare earth strengthened nickel-based alloy sample. In the present invention, the temperature during the solid solution strengthening treatment is preferably 1080-1150°C, and the time is preferably 0.8-1.4h; more preferably, the temperature is 1130°C and the time is 1h. In the present invention, during the double aging treatment, the temperature of the first aging treatment is preferably 700-740°C, and the time is preferably 7-9h; more preferably, the time is 720°C, the heat preservation is 8h, and the furnace is cooled for 2h. The temperature of the second aging treatment is 600-650°C, the time is preferably 6-10h, and more preferably, the temperature is 620°C and the heat preservation is 8h. In the present invention, the friction and wear properties of the nickel-based alloy can be improved by solid solution and double aging treatment. The present invention adds rare earth powder and adopts selective laser melting technology to perform 3D printing rapid prototyping, and performs heat treatment on the rare earth alloy obtained by selective laser melting. After a series of modification treatments, the alloy undergoes a structural phase change and generates a rare earth strengthening phase, thereby improving the overall mechanical properties of the GH4169 rare earth alloy.

[0040] The present invention also provides a GH4169 nickel-based alloy prepared by any of the methods described above, characterized in that the tensile strength of the GH4169 nickel-based alloy is ≥1980 MPa and the elongation is ≥17%.

[0041] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0042] The GH4169 alloy in the examples and comparative examples is a gas-atomized GH4169 high-temperature alloy powder provided by AVIC Matt Powder Metallurgy Technology (Beijing), with a powder particle size of 15 to 55 μm, a substantially spherical powder shape and good fluidity.

[0043] Example 1

[0044] 1. Preparation of rare earth metal powder

[0045] Weigh the rare earth metal yttrium, place the weighed powder in the reactor, close the lid and tighten it evenly. Turn on the vacuum pump to extract until the vacuum degree in the reactor reaches 1.33×10 -2 , turn off the vacuum pump; introduce hydrogen into the reactor, stop the air intake and perform pressure test and leak detection. If there is no hydrogen leakage, start the temperature control device to raise the temperature to 450°C for hydrogenation. During the reaction, stir the powder once every 1 hour; hydrogenate and keep warm for 2 hours, with the hydrogen flow rate controlled at 1.2L / min. After the reaction is completed and cooled to room temperature, discharge the hydrogen from the reactor, take the powder, and obtain hydrogenated rare earth.

[0046] The above-mentioned hydrogenated rare earth metal is placed in a reactor, and the rare earth metal-modified olefin dehydrogenation agent is placed in the reactor (the mass ratio of the hydrogenated rare earth and the olefin dehydrogenation agent is 4:3). Close the lid of the reactor and tighten it evenly. Turn on the vacuum pump to extract to 0.01Pa, start the temperature control system to raise the temperature to 450°C, react for 2 hours, and after the reaction is completed and cooled to room temperature, take out the powder to obtain dehydrogenated rare earth.

[0047] The dehydrogenated rare earth metal was dry-milled under argon conditions at a rotation speed of 400 rpm and a ball-to-material ratio of 20:1 for 60 minutes to obtain a rare earth metal powder of 250-300 meshes.

[0048] 2.GH4169 nickel-based alloy powder

[0049] GH4169 nickel-based alloy powder with a particle size of 15 to 30 μm was dried in a vacuum drying oven at a drying temperature of 60° C. for 2 hours to remove volatile impurities such as water vapor.

[0050] 3. Ball milling

[0051] Using QM-3SP4 planetary ball mill, rare earth metal powder and GH4169 nickel-based alloy powder were mixed in a mass ratio of 1:23 and put into a ball ink tank, and then 500g of glass balls were put into the ball ink tank, and the ball mill tank was symmetrically placed on the ball mill, and the cover was closed after tightening, and ball milling was performed. The speed was set to 300r / min and the time was 200min.

[0052] 4. Preparation of GH4169 rare earth reinforced nickel-based alloy samples by laser melting

[0053] The mixed material prepared in step 3 was used as the raw material, and the laser power was 1600W, the scanning speed was 10mm / s, the powder feeding rate was 1.5r / min, and the spot diameter was 2mm to prepare a test block of 10mm×10mm×10mm. The metallographic structure of the test block is as follows Figure 1 (a) shows the SEM structure. Figure 2 As shown in (a), the friction and wear coefficient is Figure 3 shown.

[0054] 5. Analysis and testing

[0055] The test block obtained in step 4 was subjected to solid solution strengthening and double aging treatment (solid solution strengthening at 1130°C for 1 hour, double aging at 720°C for 8 hours (furnace cooling for 2 hours) + 620°C for 8 hours). The metallographic structure after treatment is as follows Figure 1 As shown in (f), the SEM structure is Figure 2 As shown in (f), the friction and wear coefficient is Figure 3 shown.

[0056] Example 2

[0057] 1. Preparation of rare earth metal powder

[0058] Weigh the rare earth metal yttrium, place the weighed powder in the reactor, close the lid and tighten it evenly. Turn on the vacuum pump to extract until the vacuum degree in the reactor reaches 1.33×10 -3 Pa, turn off the vacuum pump; introduce hydrogen into the reactor, stop the air intake and perform pressure test and leak detection. If there is no hydrogen leakage, start the temperature control device to raise the temperature to 445°C for hydrogenation. During the reaction, stir the powder every 0.5h; hydrogenate and keep warm for 1.5h, with the hydrogen flow rate controlled at 1.5L / min. After the reaction is completed and cooled to room temperature, discharge the hydrogen from the reactor, take the powder, and obtain hydrogenated rare earth.

[0059] The above-mentioned hydrogenated rare earth metal is placed in a reactor, and the rare earth metal-modified olefin dehydrogenation agent is placed in the reactor (the mass ratio of the hydrogenated rare earth and the olefin dehydrogenation agent is 5:4). Close the lid of the reactor and tighten it evenly. Turn on the vacuum pump to extract to 0.01Pa, start the temperature control system to raise the temperature to 445°C, react for 4 hours, and after the reaction is completed and cooled to room temperature, take out the powder to obtain dehydrogenated rare earth.

[0060] The dehydrogenated rare earth metal was dry-milled under argon conditions at a rotation speed of 400 rpm and a ball-to-material ratio of 20:1 for 60 minutes to obtain a rare earth metal powder of 250-300 meshes.

[0061] 2.GH4169 nickel-based alloy powder

[0062] GH4169 nickel-based alloy powder with a particle size of 30 to 55 μm was dried in a vacuum drying oven at a drying temperature of 60° C. for 2 hours to remove volatile impurities such as water vapor.

[0063] 3. Ball milling

[0064] Using QM-3SP4 planetary ball mill, rare earth metal powder and GH4169 nickel-based alloy powder were mixed in a mass ratio of 1:20 and put into a ball ink tank, and then 500g of glass balls were put into the ball ink tank, and the ball mill tank was symmetrically placed on the ball mill, and the cover was closed after tightening, and ball milling was performed. The speed was set to 300r / min and the time was 200min.

[0065] 4. Preparation of GH4169 rare earth reinforced nickel-based alloy samples by laser melting

[0066] The mixed material prepared in step 3 was used as the raw material, and a laser power of 1400 W, a scanning speed of 8 mm / s, a powder feeding rate of 1.3 r / min and a spot diameter of 2.1 mm were selected to prepare a test block of 10 mm×10 mm×10 mm.

[0067] 5. Analysis and testing

[0068] The test block obtained in step 4 was subjected to solid solution strengthening and double aging treatment (solid solution strengthening at 1150°C for 0.8h, double aging at 740°C for 7h (furnace cooling for 3h) + 600°C for 10h).

[0069] Example 3

[0070] 1. Preparation of rare earth metal powder

[0071] Weigh the rare earth metal yttrium, place the weighed powder in the reactor, close the lid and tighten it evenly. Turn on the vacuum pump to extract until the vacuum degree in the reactor reaches 1.33×10 -2, turn off the vacuum pump; introduce hydrogen into the reactor, stop the air intake and perform pressure test and leak detection. If there is no hydrogen leakage, start the temperature control device to raise the temperature to 455°C for hydrogenation. During the reaction, stir the powder once every 1 hour; hydrogenate and keep warm for 2 hours, with the hydrogen flow rate controlled at 1.0L / min. After the reaction is completed and cooled to room temperature, discharge the hydrogen from the reactor, take the powder, and obtain hydrogenated rare earth.

[0072] The above-mentioned hydrogenated rare earth metal is placed in a reactor, and the rare earth metal-modified olefin dehydrogenation agent is placed in the reactor (the mass ratio of the hydrogenated rare earth metal to the olefin dehydrogenation agent is 4:3). Close the reactor cover and tighten it evenly, turn on the vacuum pump to extract to 0.01Pa, start the temperature control system to raise the temperature to 455°C, react for 3 hours, and after the reaction is completed and cooled to room temperature, take out the powder to obtain dehydrogenated rare earth.

[0073] The dehydrogenated rare earth metal was dry-milled under argon conditions at a rotation speed of 400 rpm and a ball-to-material ratio of 20:1 for 60 minutes to obtain a rare earth metal powder of 250-300 meshes.

[0074] 2.GH4169 nickel-based alloy powder

[0075] GH4169 nickel-based alloy powder with a particle size of 15 to 30 μm was dried in a vacuum drying oven at a drying temperature of 60° C. for 2 hours to remove volatile impurities such as water vapor.

[0076] 3. Ball milling

[0077] Using QM-3SP4 planetary ball mill, rare earth metal powder and GH4169 nickel-based alloy powder were mixed in a mass ratio of 1:25 and put into a ball ink tank, and then 500g of glass balls were put into the ball ink tank, and the ball mill tank was symmetrically placed on the ball mill, and the cover was closed after tightening, and ball milling was performed. The speed was set to 300r / min and the time was 200min.

[0078] 4. Preparation of GH4169 rare earth reinforced nickel-based alloy samples by laser melting

[0079] The mixed material prepared in step 3 was used as the raw material, and a laser power of 1800 W, a scanning speed of 14 mm / s, a powder feeding rate of 1.8 r / min and a spot diameter of 1.5 mm were selected to prepare a test block of 10 mm×10 mm×10 mm.

[0080] 5. Analysis and testing

[0081] The test block obtained in step 4 was subjected to solid solution strengthening and double aging treatment (solid solution strengthening at 1080°C for 1.4h, double aging at 700°C for 9h (furnace cooling for 1.5h) + 650°C for 6h). The metallographic structure after treatment is as follows Figure 1(e) shows that the SEM structure is Figure 2 As shown in (e), the friction and wear coefficient is Figure 3 shown.

[0082] Comparative Example 1

[0083] The difference from Example 1 is that no rare earth metal powder is added. The specific operation is as follows:

[0084] GH4169 alloy powder was used as raw material, and a 10mm×10mm×10mm test block was prepared with a laser power of 1600W, a scanning speed of 10mm / s, a powder feeding rate of 1.5r / min and a spot diameter of 2mm.

[0085] The obtained test blocks were subjected to solid solution strengthening and double aging treatment (solid solution strengthening at 1130°C for 1 hour, double aging at 720°C for 8 hours (furnace cooling for 2 hours) + 620°C for 8 hours).

[0086] Comparative Example 2

[0087] The difference from Example 1 is that the amount of rare earth added is different, and the mass ratio of rare earth metal powder to GH4169 nickel-based alloy powder is 1:30. Other operations are exactly the same as in Example 1.

[0088] Comparative Example 3

[0089] The difference from Example 1 is that the parameters for preparing the GH4169 rare earth reinforced nickel-based alloy sample by laser melting are different. Specifically, the laser power is 2000 W, the scanning speed is 12 mm / s, the powder feeding rate is 1.5 r / min and the spot diameter is 2 mm, and a 10 mm×10 mm×10 mm test block is prepared.

[0090] Comparative Example 4

[0091] The difference from Example 1 is that different solid solution strengthening temperatures are used for treatment, and other operations are exactly the same as Example 1. The solid solution strengthening temperatures of 930°C, 980°C or 1030°C are used for treatment, and the metallographic structures after treatment are as follows: Figure 1 (b), 1(c), and 1(d), the SEM structures are as follows: Figure 2 (b), 2(c), and 2(d). The friction and wear coefficient is shown in Figure 3 As shown. Figure 1It can be seen that the grain size is the smallest after 930℃ solution for 1h, and there are a small number of twins in the crystal. When the solution temperature rises to 980℃, there is almost no obvious change in the organizational characteristics and grain size. When the heat treatment process conditions are 1030℃ solution for 1h, the grains coarsen and the grain size increases significantly. When the solution temperature rises to 1080℃, the δ phase is completely dissolved and a new strengthening phase begins to form. When the solution temperature rises to 1130℃, the grains are fine, the fine grains are strengthened, and the mechanical properties improve. With the increase of the solution temperature, the grain size gradually grows, and large-sized grains begin to appear; the δ phase dissolves, new strengthening phases are produced, and the comprehensive performance will improve again.

[0092] The content of δ phase will affect the hardness of the sample. The precipitation area of ​​δ phase is the grain boundary or twin that is enriched with Nb. The shape of the precipitated δ phase is short rod or needle-like. At high temperature, the morphology of δ phase is short rod, and at lower temperature, the morphology of δ phase is needle-like. Figure 2 It is the microstructure of the alloy under a scanning electron microscope, and the distribution of the phase can be clearly seen. This phase has the function of pinning the grain boundary and hindering the growth of grains. This high-hardness phase component is generally considered to be an important source of cracks, which will cause the plasticity and toughness of the high-temperature alloy to decrease. In addition, it also has a great influence on the notch sensitivity of the high-temperature alloy. Under the action of a higher solution temperature, the phase will be dissolved, resulting in an increase in the notch sensitivity of the alloy, but an appropriate amount of δ phase has a better side. Studies have shown that an appropriate amount of δ phase can effectively prevent grain boundary sliding after being precipitated in a certain direction at the grain boundary. The precipitation of an appropriate amount of phase is also beneficial to improving the impact toughness and plasticity of the alloy.

[0093] Depend on Figure 2 It can be seen that after the 980℃ solution heat treatment, the grains grow slightly, the grain boundaries are not smooth, and there are a small number of twins; after the 1080℃ solution heat treatment, the grain boundaries of the alloy become more straight, and the number of twins increases, and the grain size remains basically unchanged; and after the 1130℃ solution treatment, a small amount of carbide and other strengthening phase residues appear in the structure of the alloy material. After the material alloy has completed the solution treatment, when the precipitated phase is under load, the movement of dislocations will be hindered by the precipitated phase: the dislocation line cuts the second phase. The elements that can produce precipitation strengthening on the alloy material are mainly Nb, A1, etc. These elements make the alloy material precipitate a large amount of γ′, γ″ and δ phases inside the body when it is subjected to aging treatment. Among them, γ″ phase is the main strengthening phase, γ′ and δ phases are secondary strengthening phases, and the strengthening effect is mainly affected by factors such as the particle size, quantity, and distribution state of the precipitated phase.

[0094] Figure 2(e) shows the microstructure of the sample after solution treatment at 1080℃ for 1h and double aging treatment. By analyzing the phase diagram, it can be seen that after the heat treatment, the sample has undergone recovery recrystallization and the cellular and dendrite structures in the deposited sample are dissolved into the austenite matrix. However, its structure is still slender grains, which is because the precipitated phase δ phase and carbide phase on the grain boundary have a pinning effect.

[0095] The δ phase precipitates at 930°C, dissolves at 980°C, dissolves completely at 1080°C, and precipitates the strengthening phase at 1130°C. The samples produce solid solution strengthening and second phase strengthening at 980°C and 1130°C, which improves the mechanical properties of the alloy. Therefore, better friction and wear performance results can be obtained at these two temperatures.

[0096] Performance Testing

[0097] The performance of the alloys finally obtained from Examples 1 to 3 and Comparative Examples 1 to 4 was tested, and the specific test results are shown in Table 1.

[0098] Table 1

[0099] Tensile strength(Mpa) Elongation(%) Hardness (HV) <![CDATA[Wear resistance (g / cm 2 )]]> Example 1 2150 18.5 585.2 0.5 Example 2 2268 17.2 596.3 0.6 Example 3 2096 18.7 574.6 0.7 Comparative Example 1 1640 12.3 453.2 1.0 Comparative Example 2 1923 9.4 544.8 0.8 Comparative Example 3 1480 10.4 501.7 0.7 Comparative Example 4 (930°C) 1997 13.6 552.9 0.9 Comparative Example 4 (980°C) 1983 12.6 546.5 0.7 Comparative Example 4 (1030°C) 2004 11.4 560.6 0.8

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for improving the mechanical properties of GH4169 nickel-based alloy, characterized in that: The steps include: 1) mixing rare earth metal powder and GH4169 nickel-based alloy powder in a mass ratio of 1:20 to 25 to obtain a mixed material; 2) Using the mixed material as raw material, laser melting was used to prepare GH4169 rare earth reinforced nickel-based alloy samples; 3) The obtained GH4169 rare earth strengthened nickel-based alloy sample was subjected to solid solution strengthening and double aging treatment.

2. The method according to claim 1, characterized in that The particle size of the rare earth metal powder in step 1) is 250-300 mesh; the particle size of the GH4169 nickel-based alloy powder is 15-55 μm.

3. The method according to claim 1, characterized in that The rare earth metal powder in step 1) is prepared by the following steps: a. Place the rare earth metal in hydrogen at 445-455°C to hydrogenate and obtain hydrogenated rare earth; b. The hydrogenated rare earth and the olefin dehydrogenating agent are mixed and placed in a vacuum environment of 445 to 455 ° C for dehydrogenation to obtain a dehydrogenated rare earth; c. ball milling the dehydrogenated rare earth to obtain rare earth metal powder.

4. The method according to claim 3, characterized in that When hydrogenation is performed in step a, the hydrogenation insulation time is 1.5 to 2 hours, the hydrogen flow rate is controlled at 1.0 to 1.5 L / min, and stirring is performed every 0.5 to 1 hour during the hydrogenation process.

5. The method according to claim 3, characterized in that: The dehydrogenation time in step b is 2 to 4 hours.

6. The method according to claim 3, characterized in that In step c, ball milling is performed by nitrogen-filled dry milling.

7. The method according to claim 1, characterized in that When laser melting is used to prepare the GH4169 rare earth reinforced nickel-based alloy sample in step 2), the laser power is 1400-1800w, the scanning speed is 8-14mm / s, the powder feeding rate is 1.3-1.8r / min, and the spot diameter is 1.5-2.1mm.

8. The method according to claim 1, characterized in that In step 3), the temperature during the solid solution strengthening treatment is 1080-1150° C. and the time is 0.8-1.4 h.

9. The method according to claim 1, characterized in that: In the double aging treatment in step 3), the temperature of the first aging treatment is 700-740° C., kept warm for 7-9 hours, and furnace cooled for 1.5-3 hours; the temperature of the second aging treatment is 600-650° C., kept warm for 6-10 hours.

10. The GH4169 nickel-based alloy prepared by the method according to any one of claims 1 to 9, characterized in that: The tensile strength of the GH4169 nickel-based alloy is ≥1980 MPa, and the elongation is ≥17%.